The Optimal Diversification Strategy in Pharmaceutical Industry: Balance-centred or Hetero-centred?. (July 2021) - Kim, Keungoui; Hwang, Junseok; Jung, Sungdo; Kim, Eungdo
Due to high uncertainty of product development and business environment, firm-level diversification has been regarded as one of the most effective methods in pharmaceutical firms. In previous study, firm-level diversification was discussed by different value chains of market, product, and technology. However, in most cases, the diversification itself was adopted in a simple manner although its property contains different aspects and the results varies depending on the diversity property of selected index. In addition, the existing approach for measuring firm's product/market diversification using sales information distinguished by standard industry classification cannot provide direct implication as different strategies are made for market and product diversification. Therefore, this study examines the effects of firm-level diversification on business and innovation performances in pharmaceutical firms by considering (1) three diversification types: market, product, and technology, (2) clear separation between market and product diversification, and (3) two diversification perspectives: balance-centred and hetero-centred. For empirical analysis, an integrated firm-level data set combining from Medtrack, Orange Book, Compustat and Total Patent database is used. From the result, in case of market diversification, less market heterogeneity causes significant influence on business performance. For product and technology, a concentrated and greater heterogeneity of product diversification are turned out to promote business performance, while the more intensive and heterogeneous technology diversification has been shown to improve innovation performance.